(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2017)
An investigation was carried out on the larvicidal efficacy of four indigenous plant extracts against the 6th instar larvae of red flour beetle, Tribolium castaneum (Herbst) during the period of February to July 2016. The result revealed that all the four plant extracts were effective in checking insect infestation and had different toxic effects against the 6th instar larvae of red flour beetle. Average mortality indicated that castor plant extract showed the highest toxic effect (average mortality 57.78%) whereas the lowest toxicity (average mortality 27.46%) was found in the neem leaf extracts. The larval mortality significantly differed among all the concentrations of the plant extracts applied and the highest mortality (60.75%) was recorded in maximum concentration (10.61 mg/cm2) of the plant extract. No larval mortality was observed in untreated control up to 72 HATs. Mortality percentage was also observed directly proportional to the level of concentrations of plant extracts and to the exposure period. Probit analysis of larval mortality also revealed that the castor plant extract showed the highest toxicity at different time interval among all the plant extracts applied. Asiat. Soc. Bangladesh, Sci. 43(2): 223-232, December 2017